Health Shocks and Human Capital Accumulation: The Case of Spanish Flu in Italian Regions. Issue 9 (1st September 2016) - Percoco, Marco
Abstract : Percoco M. Health shocks and human capital accumulation: the case of Spanish flu in Italian regions, Regional Studies . The impact of health on economic development is a hotly debated issue in the economics literature, with most scholars supporting the idea that the diffusion of diseases is detrimental to development. In this context, pandemics are an important case study given their exogenous nature, which makes identification of the impact of diseases on development clearer than in other cases such as malaria or smallpox. This paper focuses on Spanish flu in Italy, one of the countries with the highest mortality rate due to the pandemic. By exploiting the regional variation in mortality and focusing on the hypothesis of the foetal origins of cognitive abilities, the long-run consequences of influenza exposure in terms of human capital accumulation are estimated. An average reduction of 0.3–0.4 years of schooling for the cohort born in 1918–20 is found. This result points to a small but persisting effect of health shocks on regional productivity through a variation in the rate of accumulation of human capital.